Estudo dos modos normais de vibração de cristais de DL-Leucina por meio de Espectroscopia Raman - Silva, José Gláucio da (2011)
Measures of Raman scattering were made on DL-leucine crystals at room temperature aiming to classify the normal vibration modes, based on group theory studies, as well as the classification of normal modes of other amino acid crystals. A study on the behavior of the DL-leucine normal modes with the temperature between 16 and 296K shows that there aren’t considerable changes on the Raman specters. This means the crystal structure is stable at the considered temperature interval, similarly to what was observed on other amino acid crystals such as L-alanine, L-isoleucine and glycine; however this stability is different than what was observed on the L-leucine crystal, which shows structural change at low temperature.